Respostas

2013-12-09T16:19:18-02:00
2x + y = 26 
x - y = 4 (x = 4 +y)

2. (4+y) + y = 26 
8 + 2y +y = 26 
8 + 3y = 26 
3y= 26 - 8 
3y= 18 
y = 6 

 x = 4 + y 
x = 4 + 6 
x = 10 

b. x - 3y = 3   (x = 3 + 3y)
    2x + 3y = 1,8 

2. (3+ 3y) + 3y= 1,8
6+ 6y + 3y = 1,8 
9y = 1,8 - 6 
9y = - 4,2 
        - 4,2 (:3)
y = -------------
          9 (:3)
          
        2,1 (:3)
 y   = ----------
         3 (:3)

y = - 0,7

x= 3 + 3y 
x = 3 + 3. (-0,7) 
x = 3 - 2,1 
x = 0,9 

                         bons estudos (:
3 3 3